Acute Kidney Injury Following Pediatric Liver Transplant. (January 2022) - Silver, Layne J.; Pan, Stephanie; Bucuvalas, John C.; Reid-Adam, Jessica A.; Oishi, Kimihiko; Ofori-Amanfo, George; Gangadharan, Sandeep
Objective: To determine the incidence, severity, and risk factors of postoperative acute kidney injury in pediatric liver transplant patients with and without inborn errors of metabolism. Design: Retrospective cohort study. Setting: Single-center PICU. Patients: All children less than or equal to 18 years old who received a liver transplant between January 2009 and July 2019. Interventions: None. Measurements and Main Results: Following exclusion criteria there were 92 transplant encounters. After excluding patients who received combined kidney-liver transplantation, acute kidney injury occurred in 57% of patients (N = 49), with 25.6% (N = 22) stage 1, 15.1% (N = 13) stage 2, and 16.3% (N = 14) stage 3. In an adjusted analysis, metabolic indication for transplant was not significantly associated with presence of acute kidney injury (p = 0.45). For the subset of patients without inborn errors of metabolism, the odds of having acute kidney injury was 1.50 (95% CI: 1.00-2.26) for each 1-unit increase in preoperative INR after adjusting for the covariates of age, preoperative albumin, CMV status of donor, and preoperative creatinine. In the full cohort, as well as the sample of children without inborn errors of metabolism, presence of acute kidney injury was associated with longer total hospital stay as well as number of ICU days. Conclusions: Acute kidney injury in the early postoperative period is common in pediatric liver transplant patients (57%), 31.4% of whom had severe disease. In patients without inborn errors of metabolism, each unit increase in preoperative INR suggests a higher risk of acute kidney injury after adjusting for covariates including preoperative creatinine. This finding suggests an association between the severity of preoperative synthetic liver function and the risk of developing postoperative acute kidney injury which requires further investigation.